The Evaluation Study of Prosperous Family Savings and Prosperous Family Business Credit in Soppeng Regency - A Amrullah; Ujang Sumarwan; Sri Utami Kuntjoro; Ali Khomsan (Media Gizi dan Keluarga, 2000)
The proposed study was to know implementation of Prosperous Family Savings (Takesra) and Prosperous Family Business Credit (Kukesra). This study was conducted in Soppeng Regency, South Sulawesi Province. The total sample was 76 women accepting Takesra and Kukesra. Takesra/Kukesra implementation processes involve inputs, process and output. The outputs of Takesra were: 1) active depositors were 26,32 % and passive depositors were 73,68 %. 2) The balance of Takesra declines from Rp. 101.435.435 to Rp. 99.777.131. The outputs of Kukesra were: 1) amount of groups accepting Kukesra increases from 140 groups to 163 groups. 2) amount of Kukesra fund rises from Rp. 210.740.000 to Rp. 281.460.000. 3) amount of groups behind in their credit payments declined from 75 groups to 64 groups. 4) amount of Kukesra outstanding declined from Rp. 58.984.493 to Rp. 55.876.084. 5) Paired Samples t Test showed that income after receiving Kukesra was different than before. The Spearman¡¦s Correlation Analysis showed that knowledge about Takesra/ Kukesra was related to attitude of participant. The Chi-Square Analysis showed that attitude of participant was related to being active of Takesra. Pearson¡¦s Correlation Analysis showed that amount of Kukesra was related to the increase income.